Sn-rich tourmaline from the Land’s End granite, SW England - Drivenes,K. (Journal of Geosciences, 2022)
Multiple generations and growth stages of tourmaline from a hydrothermal quartz-tourmaline rock from the Land’s End granite, SW England, were investigated by Electron Probe MicroAnalyzer (EPMA) to reveal details of the variation in tourmaline composition with emphasis on the distribution of Sn. Tourmaline shows a large range in chemical composition, mostly on the dravite-schorl solid solution and towards more Fe-rich compositions. Several growth zones have very high Fe levels (> 3.5 apfu) with a significant amount of Fe3+ coupled with low Al. The main substitution vectors controlling the major element composition are Fe2+Mg-1 and Fe3+Al-1. The Fe-Mg exchange is the main substitution in the earlier growth stages, whereas the Fe-Al substitution becomes more important towards the end of the crystallization sequence. Tin is commonly associated with the high Fe-zones, but all Fe-rich zones do not necessarily have elevated Sn content. Octahedral sites in tourmaline, most likely the Y-site, host Sn through the proposed coupled substitution YZSn4+ + 2YZFe2+ + 5YZFe3+ + WO2- ↔ 2YZMg2+ + 6YZAl3+ + WOH-. The thin Sn-rich zones, hosting up to 2.53 wt. % SnO2, are interpreted to coincide with the onset of cassiterite crystallization, and the lower Sn content in subsequent growth zones reflects the fluid chemistry and Sn solubility in a cassiterite-buffered hydrothermal system. This study demonstrates the suitability of quantitative X-ray mapping in identifying and quantifying minor elements in finely-spaced growth zones.
Keywords: Tourmaline; tin; trace elements; EPMA